Sistem Pendukung Keputusan Rekomendasi Penerima Beasiswa Menggunakan Fuzzy Multi Attribut Decision Making (FMADM) dan Simple Additive Weighting (SAW) - Candra Surya (Universitas Syiah Kuala, 2015)
Scholarship is a donation in term of financial assistance that is given to an individual, student or pupils. Even though, the target distribution of the scholarships is sometime not relevant. It is because the scholarship distribution has not yet used a tool or method to determine suitable scholarship recipients. For that reason, it needs to design a system to determine the scholarship recipients using Fuzzy Multi Attribute Decision Making (FMADM) and Simple Additive Weighting (SAW) method. FMADM method is used to looking for an alternative of some Alternatives with some criteria that determined before. Moreover, SAW method is used to rank the existing alternatives. The result of this research can be used as a tool to make decision with recommendation of the scholarship recipients.